The Nature of Variation in Tone Sandhi Patterns of Shanghai and Wuxi Wu - Yan, Hanbo (Frontiers in Chinese Linguistics,, 2018)
This book conducts a thorough investigation of the variation in tone sandhi patterns of Shanghai and Wuxi Wu using quantitative rating experiments. Although Shanghai Wu has been well documented, to date there has never been any quantitative study that systematically investigates the factors that influence variability - a research gap this book fills. Further, Wuxi Wu is investigated as an additional case that demonstrates the unique phonological nature of tone sandhi, and how it changes how speakers learn and internalize the variable tone sandhi pattern. The findings presented here will shed new light on important issues of wordhood, the interface of morphosyntax and phonology, and the formal model of variability in phonology.